Modern weapons and military equipment for issue 1-2017 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Slovakia unveils 8X8 Corsac IFV; DSG Technology begins production of supercavitating bullets; Wielding a bigger stick: Western advances i BVRAAM capabilities; France’s Leclerc Super-Tank: Better than American or Russian Armor?; China Stole This Fighter From Russia—and It's Coming to the South China Sea; Parting shot – Centauro II; Lynx IFV ready to stalk the export market; Remote controlled: The unmanned revolution turns to turrets.